Causes of Athletic Trainer Attrition: A Critically Appraised Topic - McKenna Tuttle; Klevione Brown; Elizabeth Starns (Journal of Sports Medicine and Allied Health Sciences: Official Journal of the Ohio Athletic Trainers' Association)
Athletic Training (AT) attrition has been a persistent issue within the profession for years. By identifying the factors contributing to the attrition rates among Athletic Trainers, targeted interventions can be developed to mitigate turnover and decrease attrition within the profession.